2014
DOI: 10.1161/circresaha.114.302614
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive Adverse Mechanical Stress Responses in Dystrophic Heart Are Coupled to Transient Receptor Potential Canonical 6 and Blocked by cGMP–Protein Kinase G Modulation

Abstract: Rationale The heart is exquisitely sensitive to mechanical stimuli in order to rapidly adapt to physiological demands. In muscle lacking dystrophin, such as Duchenne muscular dystrophy (DMD), increased load during contraction triggers pathological responses thought to worsen the disease. The relevant mechano-transducers and therapies to target them remain unclear. Objectives We tested the role of transient receptor potential canonical channels TRPC3 and TRPC6 and their modulation by protein kinase G in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 51 publications
(75 reference statements)
5
105
0
Order By: Relevance
“…Reduced channel suppression by PKG1α oxidation fits this observation. Redox sensitivity of PKG1α suppression of TRPC6 may also have therapeutic implications beyond the heart, including in dystrophinopathies (24) and glomerulosclerosis (26,27), where ROS and TRPC6 play a pathophysiological role. Future studies are needed to identify the protein partners that control PKG1α translocation and develop strategies to selectively sustain its reduced state to maximize the efficacy of its activation against myocardial disease.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…Reduced channel suppression by PKG1α oxidation fits this observation. Redox sensitivity of PKG1α suppression of TRPC6 may also have therapeutic implications beyond the heart, including in dystrophinopathies (24) and glomerulosclerosis (26,27), where ROS and TRPC6 play a pathophysiological role. Future studies are needed to identify the protein partners that control PKG1α translocation and develop strategies to selectively sustain its reduced state to maximize the efficacy of its activation against myocardial disease.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…26,47 We suspect that activation of TRPC6 is a major player in initiating this PDE5-medated cascade; however, difficulties in the measurement of murine TRPC6 leave us unable to draw that conclusion from this study. We chose the GRMD model of DMD to test the prophylactic efficacy of tadalafil on delaying cardiomyopathy because this model better recapitulates the severity of the cardiomyopathy seen in DMD compared with mdx mice, which show clinical signs of cardiomyopathy typically after age 12 months.…”
Section: Discussionmentioning
confidence: 82%
“…In a recent report, Seo et al 26 demonstrated that both genetic deletion of the nonspecific cation channel TRPC6 and sildenafil provide nearly equivalent protection against acute stretch-induced arrhythmias, an effect of calcium dysregulation in isolated mdx cardiomyocytes, suggesting that PDE5 inhibition deactivates TRPC6 permeability, thereby reducing TRPC6-mediated Ca 2+ influx. This effect is likely a result of PKG-dependent phosphorylation of TRPC6 on Thr69 (in mice; Thr70 in humans and dogs).…”
Section: Modulated Trpc6 and Protease Content In Tadalafil-treated Grmentioning
confidence: 99%
“…TRPC1 and TRPC6 have been suggested to be a component of the tarantula toxin-sensitive mechanosensitive cation channels [ 132 , 133 ]. For example, the excessive mechanical stress-induced muscle contractility in myocytes with Duchenne muscular dystrophy was blunted by inhibition or deletion of TRPC6 [ 134 ]. On the other hand, intracellular lipid mediators, such as DAG and 12-hydroxy-eicosatetraenoic acid (12-HETE), reportedly mediate TRPC6 channel activation induced by oxidative stress [ 135 ] and mechanical stretch [ 136 ].…”
Section: Structure and Function Of Trpc Channelsmentioning
confidence: 99%